Penggunaan Media Sosial Tiktok Dalam Pembentukan Karakter Remaja - Febriany, Febriany; Inzahroh, Amalia; Muna, Syiddah Naelatul (IAINU Kebumen, 2023)
In this globalization era, technology is developing more rapidly with the presence of digital systems such as the internet making it an important thing in our daily lives in education, business and social activities. One of them is the Tiktok application which affects the lifestyle and ethics of today's teenagers. The purpose of this study is to analyze the influence of the Tiktok application on character development in adolescents. The research method uses a descriptive analysis qualitative method. Data collection techniques with observation in the form of interviews. The subjects of this research are teenagers who are active in using Tiktok with ages 12 - 16 years. The results of this study indicate that the Tiktok application has a significant effect on lifestyle and ethics in adolescents ± 25%. So that the 9 pillars of character are needed in the lifestyle of adolescents in order to minimize any imbalance or misuse of the Tiktok application. This change occurs because of spontaneous motivation to do something when seeing Tiktok content posts